2017
DOI: 10.1016/j.psychres.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Seeing light at the end of the tunnel: Positive prospective mental imagery and optimism in depression

Abstract: Optimism is associated with positive outcomes across many health domains, from cardiovascular disease to depression. However, we know little about cognitive processes underlying optimism in psychopathology. The present study tested whether the ability to vividly imagine positive events in one's future was associated with dispositional optimism in a sample of depressed adults. Cross-sectional and longitudinal analyses were conducted, using baseline (all participants, N=150) and follow-up data (participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 55 publications
6
73
0
2
Order By: Relevance
“…It is also possible that individuals high in Positive Imagery Vividness were more inclined to become imaginatively involved in the pictures; this suggestion is supported by the fact that the PIT specifically measures prospective imagery (i.e., simulations of possible future scenarios). An individual's vividness of positive prospective imagery has been previously associated with optimism (Blackwell et al ., ; Ji, Holmes, & Blackwell, ), and in the context of our study, it is plausible that participants high in Positive Imagery Vividness had greater access to positive future‐oriented representations of the world that encouraged them to ‘step into’ the Project Soothe pictures. To further evaluate this idea, it would be interesting to test whether the vividness of prospective mental imagery, rather than valenced mental imagery per se , is critical to the relationship we found.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It is also possible that individuals high in Positive Imagery Vividness were more inclined to become imaginatively involved in the pictures; this suggestion is supported by the fact that the PIT specifically measures prospective imagery (i.e., simulations of possible future scenarios). An individual's vividness of positive prospective imagery has been previously associated with optimism (Blackwell et al ., ; Ji, Holmes, & Blackwell, ), and in the context of our study, it is plausible that participants high in Positive Imagery Vividness had greater access to positive future‐oriented representations of the world that encouraged them to ‘step into’ the Project Soothe pictures. To further evaluate this idea, it would be interesting to test whether the vividness of prospective mental imagery, rather than valenced mental imagery per se , is critical to the relationship we found.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, it was surprising how low the standardized beta coefficients in the regressions were (none above .06), given that the level of depressive symptoms was quite high in our sample (17% met criteria for possible depression on the PHQ‐9). This independent relationship between the positive variables echoes a recent finding that Positive Imagery Vividness predicts optimism even controlling for depression (Ji et al ., ). Our study supports the view that positive variables are dissociable from psychopathology in predicting emotional responses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One suggestion is to use the LOT–R as close as possible to diagnosis to screen patients to determine their level of optimism and to offer the women at risk a closer follow‐up in the postoperative period. Some studies have found that optimism can be altered temporarily by positive interventions, such as brief manipulations consisting of positive future thinking and positive imagery exercises; however, the durability of such alterations has not been examined. Thus, further research is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for effective procedures to evoke a positive emotional response in vulnerable populations with emotional disorder symptomatology. Interestingly, a recent study on prospective imagery in depressed individuals showed that vividness of positive prospective imagery predicted optimism levels over time [35]. Being able to vividly imagine a positive future may thus be an important 'skill' to boost optimism.…”
Section: Discussionmentioning
confidence: 99%